2009
DOI: 10.1021/jf803215t
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Activities of Chiral Thiourea Derivatives Containing an α-Aminophosphonate Moiety

Abstract: Starting from benzaldehyde 1, the title compounds 8 were synthesized in six steps. Benzaldehyde 1 was reacted with ammonium hydroxide, and the resulting imine was then treated with dialkyl phosphite 3 to give dialkyl N-(arylmethylene)-1-amino-1-aryl methylphosphonates 4. Phosphonates 4 were then easily hydrolyzed to give dialkyl 1-amino-1-aryl-methylphosphonates 6, which on treatment with triethylamine, carbon disulfide, and phosphorus oxychloride provided 7. Target compounds 8 were then prepared by the reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
78
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 147 publications
(82 citation statements)
references
References 22 publications
0
78
0
1
Order By: Relevance
“…Furthermore, pyrimidyl benzylamine derivatives, for example, N- [4-(propanoxycarbonyl)phenyl]-2-(4,6-dimethoxypyrimidin-2-yloxy)benzylamine (ZJ0273), have also been reported to show good herbicidal activities and have been commercialized in China as a prodrug herbicide [6]. Recently, α-amino phosphonic acid and their ester derivatives, as bioisosteres of natural amino acids, have received an increasing attention from the fields of medicinal chemistry and pesticide science because of their wide biological activities such as enzyme inhibitors, antibiotics, and haptens of catalytic antibodies, fungicides, herbicides, plant regulators, and plant virucides [7][8][9][10][11][12][13]. To find potent and selective herbicide lead structures, we have synthesized a series of novel pyrimidinyl benzylamine analogues containing a phosphonyl group (2) with structure similar to ZJ0273 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, pyrimidyl benzylamine derivatives, for example, N- [4-(propanoxycarbonyl)phenyl]-2-(4,6-dimethoxypyrimidin-2-yloxy)benzylamine (ZJ0273), have also been reported to show good herbicidal activities and have been commercialized in China as a prodrug herbicide [6]. Recently, α-amino phosphonic acid and their ester derivatives, as bioisosteres of natural amino acids, have received an increasing attention from the fields of medicinal chemistry and pesticide science because of their wide biological activities such as enzyme inhibitors, antibiotics, and haptens of catalytic antibodies, fungicides, herbicides, plant regulators, and plant virucides [7][8][9][10][11][12][13]. To find potent and selective herbicide lead structures, we have synthesized a series of novel pyrimidinyl benzylamine analogues containing a phosphonyl group (2) with structure similar to ZJ0273 (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…TMV is known to infect more than 400 plant species such as tobacco, tomato, potato and cucumber to cause tremendous economic loss worldwide 45,46 . Built on our previous studies in this area to treat plant virus diseases 47,48 , our preliminary studies here found that the isatin-derived alkene compound 5k showed a promising 42.6% inhibition rate against TMV infection. The positive control experiment using the commercially used drug Ningnanmycin 45,49 showed 56.2% inhibition rate (Fig.…”
Section: Resultsmentioning
confidence: 79%
“…Intermediate I was prepared according to the reported methods [26][27][28], a-aminobenzylphosphonate 5 was made by following the literature procedure [29].…”
Section: Methodsmentioning
confidence: 99%